2024
DOI: 10.1038/s41598-024-57659-x
|View full text |Cite
|
Sign up to set email alerts
|

Heat shock factor 1 inhibition enhances the effects of modulated electro hyperthermia in a triple negative breast cancer mouse model

Pedro H. L. Viana,
Csaba A. Schvarcz,
Lea O. Danics
et al.

Abstract: Female breast cancer is the most diagnosed cancer worldwide. Triple negative breast cancer (TNBC) is the most aggressive type and there is no existing endocrine or targeted therapy. Modulated electro-hyperthermia (mEHT) is a non-invasive complementary cancer therapy using an electromagnetic field generated by amplitude modulated 13.56 MHz frequency that induces tumor cell destruction. However, we have demonstrated a strong induction of the heat shock response (HSR) by mEHT, which can result in thermotolerance.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 66 publications
(90 reference statements)
0
2
0
Order By: Relevance
“…In our previous studies, we demonstrated that mEHT-induced a heat shock response (HSR) with the upregulation of HSF1 and HSP70. The concomitant inhibition of this HSR improved the anticancer effects of mEHT. , However, the drugs applied in those studies have limitations, such as the enhancement of HSPB1 phosphorylation (e.g., quercetin) and the lack of clinical application (e.g., KRIBB11) . Thus, to improve the clinical translational potency of this strategy, inhibition of mEHT-induced HSPs by FDA-approved drugs is needed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In our previous studies, we demonstrated that mEHT-induced a heat shock response (HSR) with the upregulation of HSF1 and HSP70. The concomitant inhibition of this HSR improved the anticancer effects of mEHT. , However, the drugs applied in those studies have limitations, such as the enhancement of HSPB1 phosphorylation (e.g., quercetin) and the lack of clinical application (e.g., KRIBB11) . Thus, to improve the clinical translational potency of this strategy, inhibition of mEHT-induced HSPs by FDA-approved drugs is needed.…”
Section: Discussionmentioning
confidence: 99%
“…Modulated electro-hyperthermia (mEHT) is a noninvasive adjuvant cancer treatment approved for clinical use in different cancer types. mEHT uses an amplitude-modulated, 13.56 MHz radiofrequency electromagnetic field by capacitive coupling between two electrodes surrounding the cancer. , Due to the difference in bioelectrical properties between cancerous and healthy tissues, , the electromagnetic field energy is absorbed mainly by cancer tissues, resulting in cancer-specific tissue damage. , At the cellular level, mEHT generates heat, leading to cellular stress and upregulation of HSPs . We previously demonstrated enhanced anticancer effects of mEHT by inhibiting HSP70 in vitro and heat shock factor 1 (HSF1) in vivo, utilizing the small molecule inhibitors of the heat shock response central regulator (i.e., HSF1): quercetin and KRIBB11, and by knocking down HSF1 production of the tumor cells with a CRISPR/Cas9 construct . However, quercetin and its derivatives enhance HSPB1 phosphorylation that supports cancer cell survival .…”
Section: Introductionmentioning
confidence: 99%